Magnoliophyta Division Plant Diversity (Typical) in Imogiri Bantul Nature Reserve - Mas’adah, Umi Sayyidatul; Widodo (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Indonesia is rich in biodiversity, one of which is planted. The results say Indonesia is estimated to have 25% of the world’s flowering plant species. However, not many people know what plant wealth is in Indonesia. Even the diversity of plants from the surrounding environment is sometimes ignored, even after the location is used as a protection or conservation area, but many still do not understand what is conserved in it. One of the conservation is Imogiri Nature Reserve, which is a production forest area of the Forest Office of Yogyakarta Special Region area of 11.4 ha. It is the location of the Imogiri nature reserve area is in the area of Imogiri King’s Tomb Complex located in two villages namely Wukirsari Village and Girirejo Village which belongs to imogiri sub-district, Bantul Regency. This research aims to find out and introduce the diversity of Magnoliophyta (typical) in imogiri nature reserve. Research using roaming methods consists of the stage of data retrieval and identification. Research on the plant diversity of the Magnoliophyta division (typical) in Imogiri Nature Reserve obtained data from 2 classes, namely Magnoliopsida and Liliopsida which are rare plants found around the community consisting of 15 orders, 17 families and 19 species. The typical Magnoliophyta plant is dominated by the Magnoliopsida class.